Pengembangan Media Interpretasi Non Personal sebagai Upaya Mendukung Wisata Edukasi di Obyek Wisata Taman Balekambang Kota Surakarta - Setiawan, Puguh Andhi; Oktadiana, Hera; Suheryadi, Heru (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2025)
Non-personal interpretation is the delivery of information that uses audio, audio-visual, multimedia, painting, panels and displays, sculptures so that visitors can understand directly. Balekambang Park tourism object is located in the city of Surakarta. From year to year the number of tourist arrivals to the Balekambang Park has increased, but there are still some visitors who still do not care about the environment and messages delivered through the facility in the form of non- personal interpretation media at Balekambang Park, so there are many violations and visitors do not know important information that should be able to provide education. Balekambang Park has a variety of non-personal interpretation media in the form of maps of the area, information boards, direction boards and rules and prohibitions boards that can provide new experiences and information and educate visitors to maintain the preservation of tourism objects along with the attractions and facilities in them. The results of the data from the identification of non-personal interpretation media that already exist in Balekambang Park and the distribution of questionnaires are used as a reference to make the development of non-personal interpretation media interesting and can educate visitors. The development is in the form of developing forms, designs, messages, as well as placement and additions to existing and existing interpretation media. Interpretation media developed into educational facilities include regional maps, historical information boards, regulatory and ban boards, directions boards and the addition of labels for flora and fauna as attractions in Balekambang Park.